2021
DOI: 10.1002/ehf2.13209
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on the management of heart failure: a United Kingdom patient questionnaire study

Abstract: Aims The coronavirus disease 2019 (COVID-19) pandemic has created significant challenges to healthcare globally, necessitating rapid restructuring of service provision. This questionnaire survey was conducted amongst adult heart failure (HF) patients in the United Kingdom (UK), to understand the impact of COVID-19 upon HF services. Methods and results The survey was conducted by the Pumping Marvellous Foundation, a UK HF patient charity. 'Survey Monkey' was used to disseminate the questionnaire in the Pumping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Paradoxically some studies had suggested that older people had higher resilience to the mental health impact of COVID-19 than younger generations, 25 and younger patients might in fact suffer from more anxiety due to concern over the possible impact of COVID-19 on finance and employment. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically some studies had suggested that older people had higher resilience to the mental health impact of COVID-19 than younger generations, 25 and younger patients might in fact suffer from more anxiety due to concern over the possible impact of COVID-19 on finance and employment. 26 …”
Section: Discussionmentioning
confidence: 99%
“…A survey of 1050 patients in the UK with heart failure found that 32% were reluctant to access healthcare systems and 65% reported that appointments were cancelled or postponed during lockdown [31]. A report from Uganda has demonstrated the inequalities in healthcare between HIV and hypertension.…”
Section: Interruptions To Services Access To Carementioning
confidence: 99%
“…Regarding outpatient activity, 18 indicators were identified from 8 articles (49,60,62,81,(116)(117)(118)(119). Most of the indicators concerned only to in-person outpatient activity.…”
Section: Outpatient Activity Volumementioning
confidence: 99%